Effects of warming up with lower-body wearable resistance on physical performance measures in soccer players over an 8-week training cycle - Bustos, A.; Metral, G.; Cronin, J.; Uthoff, A.; Dolcetti, J. (The Journal of Strength and Conditioning Research, 2020)
Warm-ups provide an opportune time to integrate specific movements to improve performance. This study aimed to examine the effects of adding wearable resistance (WR) lower-limb loading to a warm-up on physical performance measures in soccer athletes. Thirty-one national-level soccer players (aged 16-18 years) were matched for speed and allocated to either a WR training (WRT = 15) or an unloaded (CON = 16) group. Both groups performed the same warm-up 2-3x·wk-1 for 8 weeks with the WRT group wearing 200- to 600-g loads on their calves. Pre-training, mid-training, and post-training data were collected for 10- and 20-m sprint times, repeated sprint ability, and vertical countermovement jump (CMJ) and horizontal countermovement jump (standing long jump [SLJ]) performance. Wearable resistance training improved pre-training to post-training 10- and 20-m sprint times more than the unloaded training (effect size [ES] = -1.06 to -0.96, respectively; 60.0-66.7 vs. 18.8-37.5% > smallest worthwhile change [SWC]). Both groups decreased CMJ over the first 4 weeks (ES = 0.45) and increased CMJ performance over the second 4 weeks of training (ES = 0.27). Both the WRT and CON groups improved SLJ performance after the 8-week training block (ES = 0.85 and 0.93, respectively; 86.7 and 62.5% > SWC, respectively), yet no differences were identified between groups. These findings indicate that 8 weeks (23 sessions) of WR training appears to elicit practically meaningful improvements in accelerated sprinting and horizontal jumping performance. Strength and conditioning practitioners should consider including WR in sports where sprinting and horizontal force production are critical performance indicators.